2017
DOI: 10.5398/medpet.2017.40.3.158
|View full text |Cite
|
Sign up to set email alerts
|

The Administration of Garlic Extract on Eimeria stiedai Oocysts and the Hematological Profile of the Coccidia Infected Rabbits

Abstract: This research aimed to examine the potential of garlic as the coccidiosis control in rabbits either in vitro or in vivo. During in vitro, observed variables were rabbits oocysts that were sporulated, unsporulated, and abnormal in incubation for 3 days with the addition of garlic extract. The treatments were doses of garlic extract administration (0%, 1%, 2%, 4%, and 8%) and sulfaquinoxalline as a standard anticoccidiosis. Meanwhile during in vivo, the variables observed were the hematological profile of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Antioxidants from natural sources play a vital role in improving reproductive efficiency, immune response and health status of rabbit does (El‐Ratel et al, ). Allicin as a natural antioxidant was reported to have many biological activities for good health status, including anti‐microbial, anti‐inflammation, immunomodulatory and hypoglycaemic (Indrasanti, Indradji, Hastuti, Aprilliyani, & Rosyadi, ). According to the obtained results, oral administration of rabbit does with both allicin levels improved their reproductive efficiency (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants from natural sources play a vital role in improving reproductive efficiency, immune response and health status of rabbit does (El‐Ratel et al, ). Allicin as a natural antioxidant was reported to have many biological activities for good health status, including anti‐microbial, anti‐inflammation, immunomodulatory and hypoglycaemic (Indrasanti, Indradji, Hastuti, Aprilliyani, & Rosyadi, ). According to the obtained results, oral administration of rabbit does with both allicin levels improved their reproductive efficiency (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Blood profile represents hematologic status of animals, either plasma or blood plasma that essentially contributes to physiological process (Indrasanti et al, 2017). Blood profile of rabbits infected with various doses and subjected to challenge test with 10 3 Eimeria stiedai is presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Two ml srynge was filled with 0,30 μl EDTA and injected through vena aucularis lateral (ears) to take 2 ml blood, then placed in a box filled with ice that had been prepared (Rukayah, 2008;;Indrasanti et al, 2017).…”
Section: Blood Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Daneshyar et al (2011) reported that the inclusion of turmeric reduced thigh triglyceride, and saturated fatty acid content in the broiler. Garlic powder contains saponins, tannins, alkaloids, and flavonoids (Indrasanti et al, 2017). Kim and Kim (2011) reported that the inclusion of garlic reduced epididymal fat tissue in mice fed high-fat diet.…”
Section: Introductionmentioning
confidence: 99%